2016
DOI: 10.1007/s15010-016-0901-3
|View full text |Cite
|
Sign up to set email alerts
|

Cranial imaging findings in neurobrucellosis: results of Istanbul-3 study

Abstract: In this study, 45 % of neurobrucellosis patients had abnormal neuroimaging findings. The duration of symptoms, polyneuropathy and radiculopathy, high CSF protein level, and low CSF/serum glucose rate were associated with inflammatory findings on imaging analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
6

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
0
21
0
6
Order By: Relevance
“…Although imaging with MRI and CT can be normal, but could be fairly suggestive, with high signal white matter lesions seen in cases of meningoencephalitis, enhancing lesions, which can be periventricular, are a reported [29,30). Meningeal enhancement is seen in cases of meningitis and ventriculitis (Fig.…”
Section: Imagingmentioning
confidence: 99%
“…Although imaging with MRI and CT can be normal, but could be fairly suggestive, with high signal white matter lesions seen in cases of meningoencephalitis, enhancing lesions, which can be periventricular, are a reported [29,30). Meningeal enhancement is seen in cases of meningitis and ventriculitis (Fig.…”
Section: Imagingmentioning
confidence: 99%
“…While studies of patients with neurobrucellosis have shown the most commonly affected cranial nerve is VIII [ 1 , 10 ], and involvement of optic nerve secondary to vasculitis has been documented [ 10 , 15 , 18 ]. There are theories that these vasculitic changes may be related to an immune-mediated reaction in the CNS due to Brucella infection [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The radiological diagnosis of neurobrucellosis is based on the existence of a CNS images not explained by any other neurological disease [14] . Only 45 % of patients affected with neurobrucellosis present radiological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Only 45 % of patients affected with neurobrucellosis present radiological abnormalities. The radiological findings can be grouped in 4 categories: (i) Inflammatory lesions: cerebral abscess, granulomas and arachnoiditis, leptomeningeal lesions, basal meningeal or cranial nerves impairments, (ii) White matter impairment with or without demyelinising lesions, (ii) Vascular lesions with chronic ischemic cerebral disease, (iv) Hydrocephalus, cerebral oedema [14] .…”
Section: Discussionmentioning
confidence: 99%